Drawing enhances cross-modal memory plasticity in the human brain: a case study in a totally blind adult - Likova, Lora T. (Frontiers in Human Neuroscience, 2012)
With functional Magnetic Resonance Imaging (fMRI) of a memory-guided drawing task under both visual and blindfolded conditions, we have recently demonstrated that the primary visual cortex (V1) may play a role in implementing the visuo-spatial buffer or the sketchpad idea for working memory. We further proposed that it might however operate in a modality-independent, or amodal form, not restricted to the visual modality. In the present study, to further explore the role of V1 in non-visual memory, we eliminated not only the visual input, but all levels of visual processing by training a congenitally blind novice to draw from tactile memory. The task of tactile exploration and memorization of the image to be drawn and a scribbling control task were also included. FMRI was run before training and after the consolidation of training by the novel Cognitive-Kinesthetic method. Remarkably, the primary visual cortex of this individual, which exhibited non-specific, noisy and immature transient responses before training, was massively recruited after training in the tactile-memory drawing task; moreover, after training, V1 produced normal, full-fledged response time-courses. The results reveal the operation of a rapid learning-based plasticity recruiting the visual cortex resources in the process of learning to draw. The learning paradigm allowed us to investigate for the first time the evolution of plastic re-assignment of the visual cortex. The fact that this re-assignment occurred in a congenitally blind subject, is consistent with an amodal nature of memory involvement of V1. The results specifically imply that such key mechanism can be empowered by the process of learning to draw.